At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
all i know is you use substitution
add the two equations and post what you got.
what do you mean by add them
steps: x-y=-5 -x+4y=10 despejas x x=-5+y 5-y+4y=10 3y=5 y=5/3 ahora en x-y=-5 x-(5/3)=-5 x=-10/3
x-y = 5 -------> Equation 1 -x+4y = 10 ------------> Equation 2 Add equations 1 and 2
oh also if it helps im only in 8th grade
By `add' he means basically add each part (the parts with x, the parts with y, and the parts with neither) in each equation, and see what the resulting equation is.
No shadow fiend. The problem is different. These answers were getting jumbled up, with another post
if (3 x 4 ) = 12 and (5 x 4) = 20, then when we add the equations we get (3 x 4) + (5 x 4) = 12 + 20 12 + 20 = 32 32 = 32. so it checks out. similarly add your equations,
meaning (x-y) +(-x+4y) = -5 + 10
wow this is even more confusing now
what is confusing about this?
So, norbeybarajas gave another good answer, both will lead you to the same path. If you add the two equations up, you'll see that the x disappears and you can solve for y.
ok thx for the answers not confusing any more
do you understand that if a = b and c = d, then a+c will be equal to b+d?
Rock it. Make sure you click `good answer' next to the answers that were helpful :)
alright can do
okay, so that is exactly what I did in your equation. I saw that one equation had x and the other equation had -x. so I knew that if i added them up, the x will cancel each other out, leaving me only with y. which means i can solve for y.
once I solve for y, all i need to do is substitute it in one of the equations and get x.